SEASONAL VARIATIONS IN PROGESTERONE SECRETIONS IN PREGNANT AND NON-PREGNANT AARDI GOATS IN THE SEMI-ARID REGION OF SAUDI ARABIA - Mohamed J. Al-Hassan (Journal of Animal and Plant Sciences, 2018)
In this study, the effects of heat stress on the secretory activity of corpus luteum were evaluated by measuring serum progesterone (P4) concentrations on day 15, 23, and 35 after natural mating. Thirty healthy mature Aardi goats were examined during summer and another 30 during winter, using the Ovsynch protocol and natural mating with tested fertile bucks. Pregnancy was verified with ultrasonography at 23 and 35 days. Pregnancy rates did not differ between summer (54.1%) and winter (56.9%). However, serum P4 was significantly ( p<0.001) higher in pregnant than non-pregnant goats at all time-points, irrespective of season. Serum P4 did not differ between summer and winter groups in pregnant goats but differed significantly (p<0.001) between two seasons in non-pregnant goats on days 15, 23, and 35 post mating. In conclusion, conception did not differ between summer and winter. Heat stress significantly alters corpus luteum activity, as reflected by decreased serum P4 concentrations in non-pregnant goats during summer, but it did not affect pregnant goats. stress, which is reflected by a lower plasma P4
Keywords: Corpus luteum; Summer; Winter; Ovsynch; Progesterone; Aardi goats.